Accidental Intrathecal Injection of Tranexamic Acid - Khaled Mahmoud; Amany Ammar (Case Reports in Anesthesiology)
Tranexamic acid (TXA) is a popular antifibrinolytic drug that is commonly used in patients with bleeding disorder. Major morbidities and mortalities have been reported following inadvertent intrathecal injection of TXA. In this paper, inadvertent intrathecal injection of TXA has resulted from similarities in appearance between TXA and heavy bupivacaine 0.5% ampoules. The patient experienced severe pain in the back and gluteal region upon injection in association with systemic hypertension and tachycardia followed by generalized myoclonic seizures and ventricular fibrillation.